Ocena związku między rozwojem fizycznym dziecka 6-letniego a stresem i jakością życia - Trambacz, Sylwia (My University, 2014)
Celem pracy była ocena związku między rozwojem fizycznym dziecka 6-letniego a stresem i jakością życia, w szczególności: ocena rozwoju fizycznego oraz częstości występowania problemów zdrowotnych, zbadanie poziomu jakości życia zależnej od zdrowia i doświadczania stresu przez dzieci oraz ocena różnicującego działania poziomu jakości życia i natężenia stresujących wydarzeń życiowych na przebieg rozwoju fizycznego i stan zdrowia dzieci. Badaną grupę stanowiło 351 dzieci, w tym 176 dziewcząt i 175 chłopców, pochodzących z Wielkopolski (z Poznania, ze średnich miast i wsi). Badania miały charakter longitudinalny. Pomiary przeprowadzono pięciokrotnie, w półrocznych odstępach czasowych. Dokonano pomiaru dziewięciu cech somatycznych: wysokości ciała, masy ciała, obwodów: ramienia, uda, pasa i bioder oraz trzech fałdów skórno-tłuszczowych. Zmierzono także ciśnienie tętnicze krwi i wykonano analizę składu ciała metodą bioimpedancji elektrycznej. Posługując się odpowiednimi kwestionariuszami ankietowymi przeprowadzono badania jakości życia i stresu, a od rodziców badanych dzieci zebrano dane dotyczące przebiegu ciąży, stanu zdrowia dziecka i statusu społeczno-ekonomicznego rodziny. Analizy statystyczne wykonane zostały w pakiecie statystycznym IBM SPSS wersja 21 oraz Statistica wersja 10. W programie AUXAL wykreślono krzywe wzrastania wysokości ciała wygładzone modelem matematycznym BTT. Wykreślono także krzywe wzrastania masy i wysokości ciała w badanym okresie za pomocą linearyzowanej regresji nieliniowej. Jakość życia większości dzieci była na wysokim poziomie, zarówno w sferze fizycznej, jak i psycho–społecznej. Poziom jakości życia nie zależał od płci dziecka, natomiast środowisko życia dziecka określone miejscem zamieszkania zdefiniowanym poziomem urbanizacji tak – dzieci z Poznania miały przeciętnie gorszą jakość życia w sferze fizycznej niż dzieci z mniejszych miejscowości. Odsetek dzieci z Poznania, odznaczających się wysokim poziomem występowania stresujących wydarzeń życiowych był większy niż dzieci z pozostałych miejscowości. Większe natężenie występowania objawów somatycznych i behawioralnych mogących być wskaźnikami odczuwanego stresu, stwierdzono u dzieci z Poznania. Stres i jakość życia mogą modyfikować przebieg rozwoju fizycznego i wartości osiąganych cech somatycznych. Związek taki został stwierdzony pomiędzy jakością życia i stresem a dystrybucją tkanki tłuszczowej.

Stress is an integral part of human life. Mechanism linking psychological stress and biological and physiological reactions has been well known. The physiological responses to stress have been associated with the activation of sympathetic and adreno–medullary (SAM) system and the hypothalamic pituitary–adrenocortical (HPA) axis. Long–term exposure to stressful conditions at school, peers and family environment affects biological defensive mechanisms (immune, metabolic and neural). A large body of evidence confirms an association between psychosocial stress and physical growth, as well as mental and physical health. Health is a complex concept with many components, it is a state of complete physical, mental and social well–being. Health–related quality of life (HRQOL) refers to the impact of an individual’s health on perceptions of health on their quality of life. Pediatric HRQOL has been defined as a multidimensional construct that is a state of complete physical, mental and social well–being for a child. The main aim of the study was to assess the association between stressful life events, health–related quality of life and physical growth in children aged 6–8. Particularly, to examine: 1. the influence of stressful life events and HRQOL to the patterns of physical growth; 2. sex differences in the level of HRQOL and stressful life events; 3. rural–urban differences in the level of HRQOL and stress. The studied sample consisted of 175 boys and 176 girls, students of grammar schools in Wielkopolska region. Participants were randomly selected and examined five times during the longitudinal study. Data were collected between Autumn 2011 and Autumn 2013. In purpose to assess the children’s physical growth, anthropometric measurements of body height, body weight, three skinfolds thickness and body circumferences (waist, arm, hip and tight) were taken. Bioelectrical impedance analysis was used twice to evaluate body composition like fat mass and fat–free mas. The PedsQL™4.0 adapted to polish conditions was used to assess the health–related 153 quality of life. Participants answered each question on a 1–3 Likert–type self–report scale, from never to almost always, where never means ‘no problem’. During the face–to–face interviews children also provided their stressful life events and described the rate of their behavioural and somatic reactions. Additionally, parents of participants were asked to describe their socioeconomic status including: parental education, place of residence and housing conditions. Parental questionnaires were also used to assess the frequency of illnesses experienced by children. Computations were running in SPSS 20 and Statistica 10.0 Software using both cross – sectional and longitudinal approach. Statistical analysis of data comprised of unidimensional and multidimensional methods. Individual body height data were fitted to mathematical model BTT. The procedures for fitting growth curves were implemented in the AUXAL programme. Most children had high level of health–related quality of life. There were no differences between boys and girls in the level of HRQOL. Children living in Poznan were more likely to have worst HRQOL, compared to their peers living in the other cities and countryside. The level of stressful life events was associated with the level of HRQOL. The rate of children’s behavioural and somatic reactions and stressful life events was higher in children from Poznan. Strong link between stressful life events and behavioural reactions was observed in boys and girls. There were significant associations between stress, health–related quality of life and fat distribution measured by waist–to–height ratio. The findings revealed, that physical growth, in particular fat distribution could be modify by both health–related quality of life and stress.
Assessment of association between stress, health-related quality of life, and physical growth – a longitudinal study of children aged 6 to 8
Wydział Biologii: Instytut Antropologii/Zakład Biologii Rozwoju Człowieka
Keywords: dzieci; children; stresujące wydarzenia życiowe; stressful life events; jakość życia zależna od zdrowia; health–related quality of life; rozwój fizyczny; physical growth; stan zdrowia; health status